Isosceles Triangles

Geometry Level pending

In the diagram above points A , C A,C and F F are collinear, point B B lies on

A C \overline{AC} and point E E lies on A D \overline{AD} and C D C E B E A B = a \overline{CD} \cong \overline{CE} \cong \overline{BE} \cong \overline{AB} = a and m F C D = 6 0 m\angle{FCD} = 60^{\circ}

Let P E B C P_{\triangle{EBC}} be the perimeter of E B C \triangle{EBC} and A A C D A_{\triangle{ACD}} be the area of A C D \triangle{ACD} .

If the value of a a for which A A C D + P E B C = 1 A_{\triangle{ACD}} + P_{\triangle{EBC}} = 1 can be expressed as

a = α β α α α a = \dfrac{\sqrt{\alpha * \beta} - \sqrt{\alpha} - \alpha}{\alpha} , where α \alpha and β \beta are coprime positive integers, find α + β \alpha + \beta .


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Feb 23, 2021

First we need to obtain θ \theta to get the measure of the desired angles to obtain the area and perimeter.

m E C D = 18 0 2 θ , m E C B = 2 θ 6 0 , m B E C = 30 0 4 θ m\angle{ECD} = 180^{\circ} - 2\theta, m\angle{ECB} = 2\theta - 60^{\circ}, m\angle{BEC} = 300^{\circ} - 4\theta

m A B E = 24 0 2 θ , m A E B = 3 θ 12 0 m\angle{ABE} = 240^{\circ} - 2\theta, m\angle{AEB} = 3\theta - 120^{\circ} and m A = 6 0 θ m\angle{A} = 60^{\circ} - \theta \implies

6 0 θ = 3 θ 12 0 θ = 4 5 m E C D = 9 0 60^{\circ} - \theta = 3\theta - 120^{\circ} \implies \theta = 45^{\circ} \implies m\angle{ECD} = 90^{\circ}

and m A = m A E B = 1 5 m A B E = 15 0 m\angle{A} = m\angle{AEB} = 15^{\circ} \implies m\angle{ABE} = 150^{\circ}

E C D \triangle{ECD} is a ( 4 5 , 4 5 , 9 0 ) (45^{\circ},45^{\circ},90^{\circ}) triangle E D = 2 a \implies \overline{ED} = \sqrt{2}a

and in A B E \triangle{ABE} :

A E 2 = 2 a 2 ( 1 cos ( 15 0 ) = 4 a 2 sin 2 ( 7 5 ) A E = 2 a sin ( 7 5 ) = 3 + 1 2 a \overline{AE}^2 = 2a^2(1 - \cos(150^{\circ}) = 4a^2\sin^2(75^{\circ}) \implies \overline{AE} = 2a\sin(75^{\circ}) = \dfrac{\sqrt{3} + 1}{\sqrt{2}}a

A D = A E + E D = 3 + 3 2 a \implies \overline{AD} = \overline{AE} + \overline{ED} = \dfrac{3 + \sqrt{3}}{\sqrt{2}}a and h = a sin ( 4 5 ) = a 2 h = a\sin(45^{\circ}) = \dfrac{a}{\sqrt{2}} \implies

A A C D = 3 + 3 4 a 2 \boxed{A_{\triangle{ACD}} = \dfrac{3 + \sqrt{3}}{4}a^2}

For P E B C P_{\triangle{EBC}} :

B C 2 = 2 a 2 ( 1 cos ( 12 0 ) = 4 a 2 sin 2 ( 6 0 ) B C = 2 a sin ( 6 0 ) = 3 a \overline{BC}^2 = 2a^2(1 - \cos(120^{\circ}) = 4a^2\sin^2(60^{\circ}) \implies \overline{BC} = 2a\sin(60^{\circ}) = \sqrt{3}a

and B E = E C = a P E B C = ( 3 + 2 ) a \overline{BE} = \overline{EC} = a \implies \boxed{P_{\triangle{EBC}} = (\sqrt{3} + 2)a}

A A C D + P E B C = 1 ( 3 + 3 ) a 2 + 4 ( 3 + 2 ) a 4 = 0 A_{\triangle{ACD}} + P_{\triangle{EBC}} = 1 \implies (3 + \sqrt{3})a^2 + 4(\sqrt{3} + 2)a - 4 = 0 \implies

dropping the negative root we have:

a = 2 ( ( 3 + 2 ) + 5 ( 3 + 2 ) ) 3 + 3 = a = \dfrac{2(-(\sqrt{3} + 2) + \sqrt{5(\sqrt{3} + 2)})}{3 + \sqrt{3}} = 2 ( 3 ( 3 ) + 30 ( 2 3 ) ( 2 + 3 ) ) 6 \dfrac{2(-3 - \sqrt(3) + \sqrt{30(2 - \sqrt{3})(2 + \sqrt{3})})}{6}

= 30 3 3 3 = 3 10 3 3 3 = α β α α α = \dfrac{\sqrt{30} - \sqrt{3} - 3}{3} = \dfrac{\sqrt{3 * 10} - \sqrt{3} - 3}{3} = \dfrac{\sqrt{\alpha * \beta} - \sqrt{\alpha} - \alpha}{\alpha} \implies

α + β = 13 \alpha + \beta = \boxed{13} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...